1960
DOI: 10.3171/jns.1960.17.6.0984
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Relationship Between the Volume and the Size of the Orifice of Experimental Aneurysms

Abstract: The purpose of this investigation was to evaluate the functional relationship between the volume and the size of the orifice of small saccular aneurysms such as those found intracranially. There is reason to believe that the relationship between those individual values plays an important,though as yet undefined, part in intra-aneurysmal hemodynamics. Little note is made in the literature of interior aneurysmal measurements save as depicted in drawings or arteriographically. While arteriorgraphy is of value in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
1

Year Published

1967
1967
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(54 citation statements)
references
References 4 publications
0
53
1
Order By: Relevance
“…Still, in 6 of the 8 aneurysms with 2 follow-up studies, the VOR was higher than the value of 28.3, above which, in Black and German's report, all experimental aneurysms thrombosed spontaneously. 30 The difference between their results and ours is likely because of the difference of parent artery-aneurysm geometry (sidewall versus bifurcation or terminal), which significantly affects intra-aneurysmal hemodynamics. 31 We believe further investigation for flow analysis (eg, computational fluid dynamics study) by using our model would be helpful for understanding a part of the natural history of giant aneurysms.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Still, in 6 of the 8 aneurysms with 2 follow-up studies, the VOR was higher than the value of 28.3, above which, in Black and German's report, all experimental aneurysms thrombosed spontaneously. 30 The difference between their results and ours is likely because of the difference of parent artery-aneurysm geometry (sidewall versus bifurcation or terminal), which significantly affects intra-aneurysmal hemodynamics. 31 We believe further investigation for flow analysis (eg, computational fluid dynamics study) by using our model would be helpful for understanding a part of the natural history of giant aneurysms.…”
Section: Discussioncontrasting
confidence: 47%
“…Kerber et al demonstrated that the use of preoperative aspirin made no difference in the patency rate of experimental aneurysms. 24 Learning from the experience of Black and German, who established a relationship between experimental aneurysm thrombosis and the ratio of aneurysm VOR, 30 in our study, we tried to make the ostium as large as possible when creating an aneurysm. More than 300 canine venous pouch bifurcation aneurysms have been created in our laboratory, and the diameters of the ostium usually have been adjusted to 6 mm, compared with an aneurysm height of 10 mm (we have no data as to the aneurysm volume in most of these aneurysms).…”
Section: Discussionmentioning
confidence: 99%
“…Intraluminal thrombosis is the function of a critical ratio between the volume of the aneurysm and its neck diameter. 6 Hence, larger aneurysms are more likely to thrombose. Meanwhile, intramural thrombus is thought to result from recurrent nontransmural dissections that lead to subadventitial bleeding and organized hematoma formation.…”
Section: Discussionmentioning
confidence: 99%
“…3 In this case, the ratio was approximately 90. Recanalization of the ICA following occlusion secondary to spontaneous thrombosis of a giant aneurysm has not been previously reported.…”
Section: 211-14mentioning
confidence: 94%